Greece in Economic Crisis: The Case of Health and Education - Xeni Dassiou (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
In 2010 the Greek economy entered a deep economic crisis. This was the result of an accumulation of structural problems in the economy, including overspending and loss of competitiveness during the previous decades, translating into persistently large budget and trade deficits. In 2015, under its third EU and IMF bailout, Greece has entered a spiral of depression that has led to its economy shrinking by one-third and unemployment skyrocketing to more than 25 percent, both a result of the austerity measures introduced as required to receive bailout funding. As a consequence, the health and education sectors have each experienced a reduction in public spending of more than one-third. We look at these two sectors before the crisis in the early 2000s, finding that a combination of delays, lack of enforcement, and reversals of urgently needed reforms resulted in obvious weaknesses not being corrected. This has prevented these two systems from delivering the social principles of equity in provision, equal opportunities for all, universal coverage, accessibility, and affordability. Healthcare and education both lack oversight and evaluation mechanisms to ensure quality of service for its users. Additionally, there are no cost containment/efficiency mechanisms on the procurement side to avoid wasting taxpayers' money and valuable resources. This means that Greece has high cost/low outcome education and health systems. When the economic crisis struck, the ability of these two systems to deliver the above mentioned social objectives further deteriorated, as lower per capita spending on education, health and social protection lowered entitlements, benefits, and outcomes while increasing the burden of out of pocket expenses, user charges etc. We conclude by arguing that there is a need for a radical change in the institutional framework and governance of these two systems, by establishing truly independent regulators or agencies, answerable only to parliament) that can effectively exercise oversight over both the quality and the cost in the provision of health and education.
Keywords: I11; I18; I21; I28; 330; Reforms; evaluation; regulation; equity; austerity